Letter from Frederick Sylvester & Brother to James Curtis Booth, October 28, 1880 - Frederick Sylvester & Brother (1880)
A follow-up to the letters of August 13 and 19 to James Curtis Booth (1810-1888) concerning the sale of some property. A bill for the services of Frederick Sylvester & Brother is rendered.
Keywords: Booth, James Curtis, 1810-1888; Real property; Frederick Sylvester & Brother; Sylvester, F.